Pengendalian Tata Ruang Kawasan Pertambangan Terhadap Kegiatan Pertambangan Emas Ilegal di Kabupaten Pidie - Hardi, Muhammad; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Pidie District is one of the areas in Aceh Province which is rich in minerals such as gold, copper, iron sand, and other metal minerals. The potential for the mine has created a lot of illegal gold mining activities that cause negative effect for the spatial planning and the environment. The local government has been trying to control and supervision, but still not able to cope with illegal gold mining activities in the study area.Seeing these conditions, the authors conducted research entitled Spatial Control of Mining Areas Against Illegal Gold Mining Activity In Pidie District. This study uses qualitative and quantitative research methods (mixed methods) and supported by ArcGIS 10.2 software to perform analysis.The study found a violation of spatial due to illegal gold mining activities that enter the protected forest areas, forest production and residential area that is not worth mine. Control efforts such as zoning, permits, incentives, disincentives, sanctions and regular monitoring has been carried out. The constraints such as government officials and companies involved, weak law enforcement and a lack of coordination among agencies makes illegal gold mining region of the study is still ongoing. Arrangement of WPR on location technically feasible, completion of the poverty problem perpetrators, and to improve inter-agency coordination are measures to control illegal gold mines in the region of study.Â Â